Legal forms of modern destination management organization and their influence on the range tasks and responsibilities - Jacek Borzyszkowski (UTMS Journal of Economics, 2013)
This article presents possible legal and organizational forms of modern destination management organizations (DMO) on the one hand, and their influence on the potential range of the tasks and responsibilities of these organizations on the other. In the article, theoretical issues were referred to; also, the results of the research by the author and other scholars were made use of. An analysis of the available sources demonstrated that modern DMOs occur in various legal and organizational forms, even though public and private partnerships of different of with a non-profit nature are most frequently met. An analysis of regional organizational structures in tourism on the example of Poland explicitly demonstrated that their legal form defines to a significant extent the range of their tasks. Thereby, it was proved that a given entity is clearly oriented towards the realizations of the tasks attributed it, while other tasks are realized either in a limited scope or they are simply 'reserved' to other entities.
Keywords: L31; L32; L83; 330; destination management organizations; legal form; tasks